Model Environmental Governance Pascabencana dalam Pemulihan Infrastruktur Pendidikan dan Air Bersih di Aceh Tamiang - Muhammad Natsir; Siti Sahara; Jasnimal Ultri; Bagus Rayuda Samiran (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Post-disaster recovery of educational infrastructure and clean water services requires collaborative and adaptive environmental governance to ecological damage. This community service aims to analyze and formulate a post-disaster environmental governance model in the recovery of educational infrastructure and clean water at MAN 1 Aceh Tamiang after flash floods and landslides. The community service uses a qualitative approach with a case study design. Data were obtained through observation, semi-structured interviews, documentation, online news, and social media related to school rehabilitation and clean water services. Data analysis was conducted using the Miles, Huberman, and Saldaña model through the stages of data reduction, data presentation, and thematic conclusion drawing. The results of the community service show that the recovery of schools and clean water services was carried out through the involvement of various actors, such as the community, volunteers, schools, local governments, and technical service providers. Rehabilitation included cleaning up approximately one meter of mud, restoring classrooms, rehabilitating sanitation facilities, repairing water supply lines, drilled wells, and traditional ring wells. The observation results found that the existence of physical infrastructure does not guarantee the functioning of services if it is not supported by integrated and responsive rehabilitation governance. Based on these findings, this Community Service Program proposes a collaborative environmental governance model that emphasizes intersectoral coordination, community participation, resilient clean water services, and strengthening post-disaster educational resilience. This model is expected to serve as a strategic approach to basic infrastructure rehabilitation in disaster-prone areas.